Relative effects of design, integration and information sharing on supply chain performance - Sezen, Bülent (Emerald Group Publishing Ltd, 2008)
Purpose - The aim of this study is to empirically investigate the relative effects of supply chain integration, supply chain information sharing and supply chain design on supply chain performance. Design/methodology/approach - Data collected from 125 manufacturing firms in Turkey are used for analyzing the relationships between the study variables. Regression analyses are used to find the relative impacts of predictor variables (design, integration and information sharing) on flexibililty, resource and output performances of a supply chain. Findings - According to the results of regression analyses, the only significant effects on resource and output performances belong to supply chain design. integration and information sharing are correlated with performance measures, but their relative effect sizes are lower than supply chain design. Originality/value - The construct of supply chain design developed in this study reveals a significant impact on resource and output performances of a supply chain. Therefore, this study can be viewed as an attempt to increase the level of awareness on supply chain design issues.
Keywords: distribution channels and markets; design; integration; information exchange; supply chain management; Turkey